2018
DOI: 10.32400/gc.13.02.19267.2018
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Skeptisme Profesional Dan Pengalaman Auditor Terhadap Kemampuan Auditor Eksternal Dalam Mendeteksi Kecurangan (Survei Pada Auditor BPK Ri Perwakilan Sulawesi Utara)

Abstract: External auditor is an independent and competent person who can examine financial statements and be responsible for the opinions given. This research aims to examine the effect of professional skepticism and auditor’s experience on fraud detection ability of external auditor. The sample in this research are all auditors who work in Badan Pemeriksa Keuangan (BPK) Republik Indonesia (The Indonesia’s Supreme Audit Institution) Reprensentative of North Sulawesi Province. The data of this research is using primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 0 publications
1
6
1
15
Order By: Relevance
“…The auditor's experience will have an impact on the existence of a better understanding so that the auditor can provide a logical explanation for the misstatement of financial statements; classify errors based on audit objectives and the underlying accounting structure (Agoes, 2012). Research (Rahmawati and Usman, 2014;Adnyani et al, 2014;Muchlis, 2015;Biksa and Wiratmaja, 2016;Arsendy, 2017;Yusrianti, 2015;Suryanto et al, 2017;Putra, 2017;Mokoagouw et al, 2018) found that auditor work experience had a significant positive impact on fraud detection.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The auditor's experience will have an impact on the existence of a better understanding so that the auditor can provide a logical explanation for the misstatement of financial statements; classify errors based on audit objectives and the underlying accounting structure (Agoes, 2012). Research (Rahmawati and Usman, 2014;Adnyani et al, 2014;Muchlis, 2015;Biksa and Wiratmaja, 2016;Arsendy, 2017;Yusrianti, 2015;Suryanto et al, 2017;Putra, 2017;Mokoagouw et al, 2018) found that auditor work experience had a significant positive impact on fraud detection.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…The process of examining client financial statements is done by evaluating audit evidence, conducting critical assessments of the validity of audit evidence, questioning and critically evaluating audit evidence so that the information obtained can be useful in detecting fraud. Research (Simanjuntak, 2012;Anggriawan, 2014;Ulfa et al, 2015;Wiguna, 2015;Trinanda, 2016;Biksa & Wiratmaja, 2016;Mokoagouw et al, 2018) found that professional skepticism had a significant impact on fraud detection. Research (Suryanto et al, 2017) found that professional skepticism did not have a significant effect on the auditor's ability to detect fraud.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Hasil-hasil riset terdahulu terkait pengaruh skeptisme profesional auditor terhadap kemampuan auditor dalam mendeteksi kecurangan masih menunjukan adanya gap penelitian. Hasil riset Hartan & Waluyo, (2016), Rahmayani et al, (2014), Biksa & Wiratmaja, (2016 serta (Mokoagouw et al, 2018), menyatakan bahwa, skeptisme professional berpengaruh positif terhadap kemampuan deteksi kecurangan. Hasil riset berbeda ditunjukan oleh penelitian Lovita, (2016), Rachman, (2017) dan Ranu & Merawati, (2017) yang menyatakan bahwa skeptisme professional audit tidak berpengaruh terhadap kemampuan auditor dalam mendeteksi kecurangan.…”
Section: Gambar 1 Cpi Indonesia Tahun 2009-2018unclassified
“…Pengaruh positif skeptisme terhadap deteksi kecurangan terlihat dari beberapa hasil-hasil riset terdahulu antara lain riset Hartan & Waluyo, (2016) menemukan bahwa skeptisme berpengaruh positif terhadap deteksi kecurangan. Hasil riset ini juga didukung Rahmayani et al, (2014), Biksa & Wiratmaja, (2016 serta (Mokoagouw et al, 2018) (Indrayani et al, 2014).…”
Section: Gambar 2 Kerangka Konseptualunclassified
See 1 more Smart Citation